Kepuasan Wisatawan Terhadap Elemen Daya Tarik Wisata Pantai Kuta Lombok - Hariani, Yuni Sulpia; Suryawardani, I Gusti Ayu Oka; Surya Diarta, I Ketut (Jurnal Master Pariwisata (JUMPA), 2020)
Tourism development can be seen from two strategic development approaches, one of them is the aspect of market driven. This research is aimed 1) To identify the factors that influence the tourists’ satisfaction who have visited the Kuta Beach Lombok; 2) To analyze the relationship between tourists’ importance level and performance of tourism destination elements of Kuta Beach Lombok; 3) To determine the development priority based on tourists’ satisfaction on the performance of tourism destination elements of Kuta Beach Lombok. This research is based on quantitative method that are factor analysis and Important Performance Analysis. Sample determination in this research used purposive sampling. The number of sampel for factor analysis is 165 and 30 samples for Important Performance analysis of foreign tourists’ who have visited Kuta Beach Lombok. Data in this research were gathered by questionnaire. Factor analysis showed eight factors that affected the tourists’ satisfaction who have visited Kuta Beach Lombok that are accomodation, hospitality, transportation, public facilities, infrastructure, tourism facility, safety and price. Importance Performance analysis showed the suitability level of importance and performance of tourism destination elements of Kuta Beach Lombok have satisfied the foreign tourists. The development strategy is increasing the bad performance of tourism destination elements in quandran I and maintaining the good performance of tourism destination elements in quandran II based on the result of caretesian quandrant. Keywords: development, tourism destination, tourists’ satisfaction